The Effect of Access and Quality of Education on Economic Development in Botswana (International Journal of Business, Economics and Management, 2016)
The study investigates whether or not access and quality of education contributes to the development process and economic well being of Botswana by (1) examining the impact of access to education on economic development, (2) establishing the relationship between quality of education and economic development and (3) testing the causal relationship between education and economic development. The study uses time series data from 1980 to 2014 which was analyzed using vector error correction model and vector auto regression approaches to test both long and short run relationships respectively. The paper provides a strong background on the political economy of education in Botswana since independence to date as a departure from our current understanding in literature. Findings show that the level of access to education has a positive and significant effect on the level of economic development; there is bidirectional causality between quality of education and the level of economic development; unidirectional causality moves from economic development to access to education. The study suggests that access to education should be complemented by enhancing more employment creation to forester long term development and private investment in inventory and tangible assets should be enhanced. Attracting more foreign direct investment and maintaining low inflation improves quality of education in the short as they work through enhanced economic development.